2005
DOI: 10.1002/ejic.200500313
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly and Characterization of Grid‐Type Copper(I), Silver(I), and Zinc(II) Complexes

Abstract: The reactions of ligand L, which comprises two bidentate binding units, with copper(I), silver(I), and zinc(II) lead to the self‐assembly of the expected supramolecular architectures 1–3, respectively, of the [2 × 2] grid type, containing four ions in tetrahedral coordination sites. The grid‐type structures are assigned on the basis of the spectroscopic data in solution, and confirmed in the solid state in the case of complex 2 by X‐ray crystallography. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Flavones constitute one of the major classes of naturally occurring products. Synthesis of flavones and their derivatives has attracted considerable attention owing to their significant biocidal, [13] pharmaceutical [14] and antioxidant [15] activities. It has been observed that the presence of hydroxyl groups at position 5 or 7 is frequently required for higher biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Flavones constitute one of the major classes of naturally occurring products. Synthesis of flavones and their derivatives has attracted considerable attention owing to their significant biocidal, [13] pharmaceutical [14] and antioxidant [15] activities. It has been observed that the presence of hydroxyl groups at position 5 or 7 is frequently required for higher biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…21 All of the bond distances and bond angles in the ligand L are in the normal range. The pyridine ring containing N(1) atom and C (6), N(2) and C(14) atoms define a plane P1, while the other pyridine ring containing N(4) atom and C (8), N(3) and C(14) atoms define another plane P2. The dihedral angle between P1 and P2 is 9.68(2)º and the dihedral angles between the phenyl ring and the P1 and P2 are 58.31(3)º and 59.79(3)º, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the synthetic conditions of the above Zn(II) and Cu(I) complexes with those used in the earlier [2×2] grid complexes, [6][7][8][9] we found that in order to obtain [2×2] grid complexes, one must not only select the appropriate ligand, but also choose the right metal-salt. In the earlier literature, the metal-salts were not simple ones, including [Cu(CH 3 CN) 4 ]PF 6 , Cu(CF 3 SO 3 ) 2 ·C 6 H 6 , Zn(BF 4 ) 2 , AgCF 3 SO 3 , AgBF 4 , Co(BF 4 ) 2 , Fe(BF4) 2 , Mn(ClO 4 ) 2 and so on.…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…Up to date, many fascinating supramolecular structures have been obtained by using metal ions and ligands containing nitrogen-donor atoms, for instance bipyridine [1], terpyridine [2] or tetrapyridine [3], to name a few.…”
mentioning
confidence: 99%